Delayed Sleep Timing and Symptoms in Adults With Attention-Deficit/Hyperactivity Disorder: A Controlled Actigraphy Study. (2013) - Gamble, Karen L.; May, Roberta S.; Besing, Rachel C.; Tankersly, Amelia P.; Fargason, Rachel E.
Abstract : Patients with attention-deficit/hyperactivity disorder (ADHD) often exhibit disrupted sleep and circadian rhythms. Determination of whether sleep disturbance and/or circadian disruption are differentially associated with symptom severity is necessary to guide development of future treatment strategies. Therefore, we measured sleep and ADHD symptoms in participants aged 19–65 who met the DSM-IV-TR ( Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, Text Revision) criteria for ADHD and insomnia without psychiatric comorbidities by monitoring actigraphy and daily sleep logs for 2 wks, as well as the Pittsburgh Sleep Quality Index (PSQI), Epworth Sleepiness Scale (ESS), the ADHD Rating Scale (ADHD-RS), and a clinic-designed sleep behavior questionnaire. Principal components analysis identified correlated circadian- and sleep-related variables in all participants with ADHD who completed the study (n = 24). The identified components were entered into a backwards stepwise linear regression analysis, which indicated that delayed sleep timing and increased sleepiness (ESS) (but not sleep duration or sleep efficiency) significantly predicted greater severity of both hyperactive-impulsive and inattentive ADHD symptoms ( p < .05 for partial regression coefficients). In addition, combined subtypes had the most impaired age-adjusted sleep quality (PSQI scores; p < .05 compared with healthy controls; n = 13), and 91.7% of them reported going to bed late due to being "not tired/too keyed up to sleep" compared with 57.2% and 50% of inattentive and symptom-controlled participants, respectively ( p < .05). In conclusion, the results of this study suggest that ADHD symptom severity correlates with delayed sleep timing and daytime sleepiness, suggesting that treatment interventions aimed at advancing circadian phase may improve daytime sleepiness. In addition, ADHD adults with combined hyperactive-impulsive and inattentive symptoms have decreased sleep quality as well as the delayed sleep timing of predominately inattentive subtypes. (Author correspondence:rfargason@uab.edu )